The Determination of Mangrove Restoration Area using Water Quality and Substrate Parameters - Amalo, Luisa Febrina; Putra, Marfian Dwidima; Handayani, Luluk Dwi Wulan; Sumpeno, Sumpeno; Luturmas, Ruben; Suryadi, Suryadi (Media Konservasi, 2025)
Mangrove plants have a substantial impact on ecosystems, both ecologically and economically. Planting mangroves is currently considered an effective method for overcoming the degradation of mangrove forests, particularly in Sebaru Kecil Island, which has limited research. Besides natural forces contributing to the success of mangrove plantations, ecological parameters are also crucial to assessing mangrove restoration areas. The parameters include physical-chemical water quality, plankton and benthos, and substrate quality. This measurement is carried out to evaluate the level of water fertility and soil conditions at the location that will be used for mangrove planting. This research aimed to determine the feasibility of the area for mangrove restoration based on physical, biological, and chemical water quality conditions, and to provide recommendations for planting mangroves suitable for Sebaru Kecil Island based on its substrate condition. The results showed that the physical-chemical parameters of the seawater at the mangrove planting locations met the quality standards, except for nitrate. The condition of plankton and benthos showed a high diversity index, with no dominant species. Based on the substrate results and physical condition of Sebaru Kecil Island, the location is suitable for mangrove planting, and we recommend planting Rhizophora stylosa in the mangrove restoration area.